A Successful Case of Conservative Management for Iatrogenic Aortocoronary Dissection During Percutaneous Coronary Intervention - Hamamoto, Masaki; Nitta, Kazuhiro; Watanabe, Yoshikazu; Fujiwara, Takashi; Tsujiyama, Shuji; Fujii, Takashi; Shokawa, Tomoki; Maeda, Koji (Journal of Coronary Artery Disease, 2022)
Aortocoronary dissection is an infrequent yet potentially lethal complication of coronary angiography or percutaneous coronary intervention (PCI). Treatment strategies include conservative management, stent implantation, and surgical intervention. We herein report a case of iatrogenic aortocoronary dissection during PCI of the right coronary artery successfully treated by conservative management. Conservative treatment may be a potential alternative to surgical treatment for iatrogenic aortocoronary dissection with limited extension when the patient’s clinical condition is stable under strict hemodynamic management.